Experimental investigation on smoldering combustion for sewage sludge treatment: Influence of key parameters and self-sustaining limit - Xue Shen; Hui Yan; Jun Shi; Yu Tan; Han Yang; Honghao Hu; Sha Li (Case Studies in Thermal Engineering)
The disposal of sewage sludge has become a challenge in recent years. Smoldering combustion is a novel, low-energy, and promising new method for sewage sludge disposal. In this study, sawdust was used as auxiliary fuel to mix sewage sludge and sand to form a porous media fuel bed for smoldering combustion. The effects of key parameters such as moisture content, sand ratio, airflow rate, and sawdust amount on the sewage sludge smoldering characteristics were studied. And smoldering self-sustaining limits were explored to ensure stable operation in practical applications. The results showed that reducing the moisture content could improve the robustness of sewage sludge smoldering combustion and reduce the preheating time. Airflow rate and S/F ratios were the main factors controlling the peak temperature and smoldering velocity. The optimal sand-to-fuel mass ratio (S/F) was 3, not only the smoldering velocity was maximum, but also sewage sludge with less sawdust added and higher moisture content could be treated.